A Blockchain-Based Framework for IoT Data Monetization Services. (24th September 2020) - Ali, Muhammad Salek; Vecchio, Massimo; Antonelli, Fabio
Abstract: Within internet of things (IoT) research, there is a growing interest in leveraging the decentralization properties of blockchains, towards developing IoT authentication and authorization mechanisms that do not inherently require centralized third-party intermediaries. This paper presents a framework for sharing IoT data in a decentralized and private-by-design manner in exchange for monetary services. The framework is built on a tiered blockchain architecture, along with InterPlanetary File System for IoT data storage and transfer. The goal is to enable IoT data users to exercise fine-grained control on how much data they share with entities authenticated through blockchains. To highlight how the framework would be used in real-life scenarios, this paper presents two use cases, namely an IoT data marketplace and a decentralized connected vehicle insurance. These examples showcase how the proposed framework can be used for varying smart contract-based applications involving exchanges of IoT data and cryptocurrency. Following the discussion about the use cases, the paper outlines a detailed security analysis performed on the proposed framework, based on multiple attack scenarios. Finally, it presents and discusses extensive evaluations, in terms of various performance metrics obtained from a real-world implementation.